S54 Preservation of mitochondrial oxidative capacity in critically ill patients balances reduction in mitochondrial biogenesis. (14th November 2013) - Astin, R; Puthucheary, Z; Saeed, S; Velloso, C; McPhail, M; Rawal, J; Skipworth, J; Singer, M; Harridge, S; Montgomery, H; Hart, N
Abstract : Background and Aims: In severe sepsis, early mitochondrial dysfunction in skeletal muscle is associated with decreased biogenesis and adverse patient outcome. We hypothesised that reduction in mitochondrial content during critical illness would be balanced by enhanced capacity to produce ATP achieved by switching from glucose to fatty acid oxidation as the preferred metabolic substrate. Methods: 30 critically ill patients (70% male, age 56.4 ± 19.7 years, APACHE II score 22.4 ± 6.6) were prospectively recruited <24 hours following intensive care admission from August 2009 to April 2011. Quadriceps vastus lateralis muscle biopsies were taken on day 1 and 7 and concentrations of mitochondrial respiratory complex proteins and key proteins of the β-oxidation pathway were determined using a Luminex assay normalised to an internal control (NNT). Mitochondrial DNA content (mtDNA), PGC1-α, β and PPRC mRNA concentrations were determined contemporaneously by RT-qPCR. Results: There were reduction in both skeletal muscle mtDNA (p = 0.04) and PGC1-α (p = 0.02) from day 1 to day 7, with fold change in PGC1α correlated with the fold change in mtDNA (r 2 = 0.65, p < 0.001, n = 19). PGC1-β and PPRC did not change. In ICU survivors, neither PGC1-α or mtDNA fold change predicted hospital or 18 month mortality (p > 0.1). Protein levels of mitochondrial respiratory complexes I-V did not change significantly from day 1 to day 7 and mtDNA fold change did not correlate with fold change in complex I-V (p > 0.1). There was a weak positive correlation between feeding (protein delivered) and fold change in complex I (r 2 = 0.20, p = 0.014) and complex III protein level (r 2 = 0.20, p = 0.016). Overall levels of mitochondrial β-oxidation pathway proteins (CPT1, MCAD, ETF, DecR1) did not change whilst peroxisomal MEFII increased significantly (p < 0.01). Conclusion: These data suggest decreased mitochondrial biogenesis over the first week of critical illness. The increase in β-oxidation proteins combined with the lack of change in respiratory chain complex concentrations during the first week suggests that the oxidative capacity of the remaining mitochondria was enhanced with increased capacity to metabolise fatty acids. These data support our hypothesis that the decreased cellular energy utilisation accompanying decreased mitochondrial biogenesis is offset by increased capacity to produce ATP through the β-oxidation of fats.